Transnasal endoscopic removal of a pituicytoma: a case report - Teltayev, Daniyar; Tursynbekov, Torebek; Mustafin, Khalit; Kydyrov, Almas; Litvinova, Tatyana; Ashirov, Nurali; Turzhanova, Ainur; Solodovnikov, Makar; Akshulakov, Serik (Frontiers in Oncology, 2025)
Pituicytoma is an exceedingly rare tumor of the pituitary gland, classified as WHO grade 1. Its presentation varies widely, often mimicking other pituitary or sellar region tumors. This report discusses a unique case of pituicytoma in a young female presenting with a combination of visual disturbances, infertility, and endocrine dysfunction, emphasizing the role of multidisciplinary management and minimally invasive surgical techniques.